Clostridium difficile Infection Worsens the Prognosis of Ulcerative Colitis - María E Negrón; Herman W Barkema; Kevin Rioux; Jeroen De Buck; Sylvia Checkley; Marie-Claude Proulx; Alexandra Frolkis; Paul L Beck; Levinus A Dieleman; Remo Panaccione; Subrata Ghosh; Gilaad G Kaplan (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: The impact of Clostridium difficile infections among ulcerative colitis (UC) patients is well characterized. However, there is little knowledge regarding the association between C difficile infections and postoperative complications among UC patients.